POPULAÇÃO CARCERÁRIA: UMA ANÁLISE DO RELATÓRIO FINAL DO MUTIRÃO CARCERÁRIO REALIZADO PELO CONSELHO NACIONAL DE JUSTIÇA NO BIÊNIO 2010/2011 - Gabriel de Freitas Ribeiro (TRF2, 2018)
The purpose of this article is discussing some important points related to the prison population, using as its approach basis the final report about the prison system campaign, developed by National Council of Justice (CNJ), during 2010/2011. First, comments about the Brazilian prison system was made, specially, about overcrowding and rebellions. Then, the prison system campaign implemented by law nº 12.106/2009, in order to verify the prison system conditions, the social prisoner’s recovery and the criminal process progress, ensuring the suitable legal process, was analyzed. The research makes several critical analysis about the prisoner’s reality. They are, in terms, a young population, with little or no instruction, from periphery, formed, basically, by black and poor people.